A conditional RNA Pol II mono-promoter drives HIV-inducible, CRISPR-mediated cyclin T1 suppression and HIV inhibition - Srinivasan Chinnapaiyan; Maria-Jose Santiago; Kingshuk Panda; Md. Sohanur Rahman; Jessica Alluin; John Rossi; Hoshang J. Unwalla (Elsevier, 2023)
Gene editing using clustered regularly interspaced short palindromic repeats (CRISPR) targeted to HIV proviral DNA has shown excision of HIV from infected cells. However, CRISPR-based HIV excision is vulnerable to viral escape. Targeting cellular co-factors provides an attractive yet risky alternative to render viral escape irrelevant. Cyclin T1 is a critical modulator of HIV transcription and mediates recruitment of positive transcription elongation factor-b (P-TEFb) kinase for transcriptional elongation. Hence, a CRISPR-mediated cyclin T1 inactivation will silence HIV transcription, locking it in an inactive form in the cell and thereby serving as an effective antiviral and possibly effecting a functional cure. However, cellular genes play important roles, and their uncontrolled inhibition can promote undesirable effects. Here, we demonstrate a conditional inducible RNA polymerase II (RNA Pol II) mono-promoter-based co-expression of a CRISPR system targeting cyclin T1 from a single transcription unit. Co-expression of guide RNA (gRNA) and CRISPR-associated protein (Cas9) is observed only in HIV-infected cells and leads to sustained HIV suppression in stringent chronically infected cell lines as well as in T cell lines. We further show that incorporation of cis-acting ribozymes immediately upstream of the gRNA further enhances HIV silencing.